Erosional injuries inflicted by a home‐made urine collection device: a case report and beyond. Issue 1 (29th July 2015) - Chen, Tao; Li, Jie; Chen, Changsheng; Han, Ruifa; Wu, Changli; Hu, Hailong
ABSTRACT: With a progressive growth of the elderly population in China, cerebrovascular accidents are increasing rapidly. As one of the most common consequences, urinary incontinence management in a long‐term (LT) home health care (HHC) setting has been emerging as a huge challenge for society. We report here a case of erosional penile and urethral injuries identified in an elderly male patient with urinary incontinence. In this case, the improper use of an external, homemade urine collection device in a LT HHC setting may very well be responsible for the medical complications identified in this patient. Noticeably, urine collection pads had been tied with knots at the base of the penis to secure the device in the patient's routine urinary incontinence HHC practice. Eczematoid dermatitides, cutaneous ulceration and scarring erosion induced by LT excessive extrinsic compression were observed on the genitalia and perineal areas. Urinary tract infection was also confirmed by urine culture. Antibiotics were administered, and suprapubic cystostomy was performed afterwards. This case highlights the importance of careful inspection of external urine collection devices focusing on risk assessment and prevention of pressure ulceration, as well as continuous patient/caregiver education/support for proper urinary incontinence management in a LT HHC setting.